Anaphylaxis Due to Hydatid Cyst Rupture - Ülkem Koçoğlu Barlas; Nihal Akçay; Mey Talip Petmezci; Güner Özçelik; Hasan Serdar Kıhtır; Selma Fettahoğlu Üstel; Recep Akpınar; Esra Şevketoğlu (Journal of Pediatric Emergency and Intensive Care Medicine)

(untitled)
Hydatid cyst disease is still endemic in our country. It may present with non-specific complaints such as abdominal pain and jaundice as well as anaphylactic reactions due to cyst rupture. In this report, we aimed to present a case of anaphylactic shock with cyst rupture in a hydatid cyst operation. A 13-year-old male patient was admitted to our emergency department with abdominal pain. Abdominal magnetic resonance imaging was consistent with hydatid cyst lesions in the liver. After three weeks of pharmacological treatment, surgical treatment was decided. During the operation, the cyst ruptured while the posterior cyst was being removed, and then the patient developed anaphylactic shock characterized by wide spread rash, swelling and sudden hypotension. The first treatment was performed with intravenous adrenaline and steroid. Adrenalin and noradrenaline infusions were used in the pediatric intensive care follow-up. Hydatid cyst is a disease that can be easily diagnosed by simple history and non-invasive imaging methods. We decided to present this case so that early diagnosis could prevent fatal complications such as anaphylactic shock and review what should be done when faced with such a situation.